Synopsis of the results of the 2008 ECVET pilot projects : we have tried ECVET: lessons from the first generation of ECVET pilot projects - synthesis of results and project portraits - Ulicná, Daniela [Verfasser]; Luomi-Messerer, Karin [Verfasser] (GHK Consulting, 2012)
"In the period 2008-2011, ten pilot projects and one network project funded by the Lifelong Learning Programme focused on testing ECVET, the European Credit system for Vocational Education & Training. The projects all had as main objectives to implement the technical specifications of ECVET: units of learning outcomes, transfer of units of learning outcomes, ECVET points and partnerships. This consisted of the development and testing of approaches, methods and tools to work with ECVET." (Textauszug, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Europäisches Leistungspunktesystem; Implementation; Pilotprojekt